Assessment of healthcare needs of elderly population in a rural area of north Kerala- a community based cross sectional study - Raveendranath, Priyanka Prasanna; Karunakaran , Usha (International Journal Of Community Medicine And Public Health, 2024)
Background: Ageing is a natural process which brings along a number of changes in physical, psychological, hormonal as well as social conditions of an individual. To address ever growing needs of geriatric population, the first step is to identify and assess those needs. Objective of the study was to assess psychological, social and physical healthcare needs of elderly population and to determine the factors associated with it. Methods: A cross-sectional study was conducted among 250 elderly Individuals 60 years and above residing in rural area of north Kerala. Wards were selected by simple random sampling and from wards study subjects were selected by consecutive sampling. Data was collected from the study subjects by direct interview. Results: Mean age of the participant’s was 69.3±7.6 years. Majority (79%) of the study participants were having comorbidities. Majority of the study participants had good physical (84%), psychological (57%) and social health (58%). Physical health, psychological health and social health was significantly associated with marital status and living arrangement and also with each other. Psychological and social health was also associated with gender. Unmet need for vision problems was 68.7% and for hearing problems it was 85.97%. Conclusions: Majority of the study participants had good physical, psychological and social health. Physical, psychological and social health was found to be significantly associated with each other. Marital status and living arrangement were significantly associated with physical, psychological and social health. Psychological and social health was significantly associated with gender.